The Role of WebQuest in Improving Digital Literacy of Students - Nasrulloh, Alfian Ahsani; Rusydiyah, Evi Fatimatur (research, training and philanthropy institution Natural Aceh, 2025)
This study explores WebQuest's role in enhancing students' digital literacy in Islamic boarding schools, particularly at Al-Jihad Islamic Boarding School in Surabaya. Digital literacy has become an essential skill for students to adapt to the challenges and opportunities of the digital era. WebQuest, an internet-based learning method designed by Bernie Dodge, enables students to develop critical thinking skills and the ability to search, evaluate, and process information independently using digital resources. The research employed a qualitative method with a case study approach, involving 10 seventh-semester students as respondents. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model. The findings indicate that implementing WebQuest can significantly improve students' digital literacy, particularly in digital skills, ethics, and safety. Respondents also reported a better understanding of using technology effectively and ethically. The implications of this study suggest that WebQuest has substantial potential as a learning method in Islamic boarding schools to support technology integration into education. With structured guidance and relevant materials, students can be better prepared to face the digital era's demands without compromising Islamic education's values. This study contributes to the development of technology-based learning in religious educational institutions.